Correlations between available primary amines, endospore coat thickness, and alkaline glutaraldehyde sensitivity for spores of select Bacillus species. Issue 11 (29th September 2020) - Player, Jacob Kent; Despain, Justen Thalmus; Robison, Richard A.
Abstract: Alkaline glutaraldehyde (GTA) is a high‐level chemical disinfectant/sterilant and has a broad microbial kill spectrum. The precise antimicrobial mechanism of GTA remains debated. GTA kill times are extremely variable across different organisms, illustrating the need for a better understanding of GTA kill mechanisms related to different organisms. A commonly proposed GTA kill mechanism suggests that it works by cross‐linking accessible primary amines on important surface proteins. If true, the antimicrobial activity of GTA may directly correlate to the number of these available functional groups. Bacillus species form highly resistant bacterial endospores that are commonly used as one of the most stringent test organisms for disinfection and sterilization. In this study, we compared the log reduction times of alkaline GTA on spores from 4 Bacillus species to fluorescent profiles generated using Alexa Fluor™ amine‐reactive dyes. GTA kill times were also compared to mean spore coat thicknesses as measured with scanning electron microscopy (SEM). Fluorescence values generated from bound amine‐reactive dye showed a strong, positive correlation to GTA susceptibility, as measured by GTA 6‐log10 reduction times. Spore coat thickness also showed a strong, positive correlation to reduction time values. Results support the hypothesis that GTA kill times are directly related to the number of available primary amines on bacterial endospores. Results also indicated that the killing efficacy of GTA may be influenced by its ability to penetrate the spore coat to reach additional targets, suggesting that damaging important biomolecules beyond surface proteins may be involved in GTA killing mechanisms. Abstract : This study demonstrates that the availability of primary amines on 4 different Bacillus spore species correlates directly with susceptibility to alkaline glutaraldehyde disinfection, as demonstrated using amine‐reactive fluorophores and 6‐log10 reduction estimates. Additionally, it shows that alkaline glutaraldehyde susceptibility is inversely related to endospore coat thickness. This suggests that GTA penetration and the availability of primary amines play important roles in GTA killing of spores.